Strategies for evaluating ectoparasiticides in companion animals - Sutherland, Cameron James (My University, 2025)
Ectoparasites including fleas, flies, lice, mites, and ticks are targets of past, present, and future veterinary concern. Controlling ectoparasites is critical to mitigate irritation, potential allergies, and transmission of vector-borne diseases. This dissertation focuses on the process evaluating ectoparasiticides before and during market release with an emphasis on the isoxazoline drug class. Chapter 2 focuses on an in vitro strategy for ectoparasite rearing and potential use for parasiticide testing. The proposed model utilizes materials that are accessible for small-scale research groups such as universities, industries, and contract research organizations. This model is a 3D-printed artificial flea feeding system that showed success rearing multiple generations of Ctenocephalides felis fleas. The ability to rear fleas using this model would make in vitro ectoparasiticide testing more accessible to researchers regardless of budget or scale. Chapter 3 focuses on the evaluation of fluralaner oral and topical canine formulations in an off-label use-case by administering it to horses, an animal with no published pharmacokinetic data from the isoxazoline drug class. Ectoparasite control in horses is of great veterinary interest as they can be responsible for pruritus, discomfort, and/or vector-borne disease transmission. This study demonstrated that fluralaner reached a higher plasma concentration when administered orally but had a longer half-life when administered topically. This provides a starting point for finding an appropriate dose and route for developing a highly effective, long-lasting ectoparasite product for horses. Chapter 4 focuses on a post-approval marketing field study administering an oral formulation of lotilaner to animals in homes experiencing flea infestations. This study showed the ability to eliminate environmental flea infestations by focusing treatment efforts on the animals living within the house rather than broad, premises sprays. The contents of this dissertation endeavor to elucidate novel strategies for ectoparasiticide testing while also highlighting the importance of data generated from field studies.
Keywords: Ectoparasite; Ectoparasiticide; Flea; Tick; Pharmacokinetics; Isoxazoline